With or without light: comparing the reaction mechanism of dark-operative protochlorophyllide oxidoreductase with the energetic requirements of the light-dependent protochlorophyllide oxidoreductase - Silva, Pedro J. (2016)
The addition of two electrons and two protons to the C17=C18 bond in protochlorophyllide is catalyzed by a light-dependent enzyme relying on NADPH as electron donor, and by a light-independent enzyme bearing a (Cys)3Asp-ligated [4Fe-4S] cluster which is reduced by cytoplasmic electron donors in an ATP-dependent manner and then functions as electron donor to protochlorophyllide. The precise sequence of events occurring at the C17=C18 bond has not, however, been determined experimentally in the dark-operating enzyme. In this paper, we present the computational investigation of the reaction mechanism of this enzyme at the B3LYP/6-311+G(d,p)//B3LYP/6-31G(d) level of theory. The reaction mechanism begins with single-electron reduction of the substrate by the (Cys)3Asp-ligated [4Fe-4S], yielding a negatively-charged intermediate. Depending on the rate of Fe-S cluster re-reduction, the reaction either proceeds through double protonation of the single-electron-reduced substrate, or by alternating proton/electron transfer. The computed reaction barriers suggest that Fe-S cluster re-reduction should be the rate-limiting stage of the process. Poisson-Boltzmann computations on the full enzyme-substrate complex, followed by Monte Carlo simulations of redox and protonation titrations revealed a hitherto unsuspected pH-dependence of the reaction potential of the Fe-S cluster. Furthermore, the computed distributions of protonation states of the His, Asp and Glu residues were used in conjuntion with single-point ONIOM computations to obtain, for the first time, the influence of all protonation states of an enzyme on the reaction it catalyzes. Despite exaggerating the ease of reduction of the substrate, these computations confirmed the broad features of the reaction mechanism obtained with the medium-sized models, and afforded valuable insights on the influence of the titratable amino acids on each reaction step. Additional comparisons of the energetic features of the reaction intermediates with those of common biochemical redox intermediates suggest a surprisingly simple explanation for the mechanistic differences between the dark-catalyzed and light-dependent enzyme reaction mechanisms.